The mirror & the light [large type] - Mantel, Hilary, 1952- (Mantel, Hilary, 1952-. Thomas Cromwell trilogy, 2020)
"England, 1536. In the wake of Anne Boleyn's execution, Thomas Cromwell continues his climb to power and wealth. Meanwhile, Henry VIII settles into brief happiness with Queen Jane Seymour. With no family or private army backing him, Cromwell must rely upon his wits. Despite rebellion at home, traitors plotting abroad, and the threat of invasion, Cromwell imagines a new country in the mirror of the future. But can a nation, or a person, shed the past like a skin? Do the dead unbury themselves? And, as the Spanish ambassador asks Cromwell, what will you do when the king, as is his wont, eventually turns on you?"--Page 4 of cover.